2009
DOI: 10.1111/j.1467-9280.2009.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Fear Extinction to an Out-Group Face

Abstract: Conditioning studies on humans and other primates show that fear responses acquired toward dangerrelevant stimuli, such as snakes, resist extinction, whereas responses toward danger-irrelevant stimuli, such as birds, are more readily extinguished. Similar evolved biases may extend to human groups, as recent research demonstrates that a conditioned fear response to faces of persons of a social out-group resists extinction, whereas fear toward a social in-group is more readily extinguished. Here, we provide an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
125
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 12 publications
(22 reference statements)
17
125
1
Order By: Relevance
“…For example, Olsson et al [50] demonstrated that conditioned fear (measured via skin conductance response) towards facial displays of individual exemplars of racial outgroups resist extinction, whereas conditioned fear towards ingroup exemplars readily extinguish. Navarrete et al [51] extended these findings by demonstrating that conditioned fear towards faces of outgroup exemplars resists extinction solely when the outgroup targets are male and not female, which is consistent with the male warrior hypothesis.…”
Section: Fear and Prejudice Against Outgroup Malesmentioning
confidence: 57%
“…For example, Olsson et al [50] demonstrated that conditioned fear (measured via skin conductance response) towards facial displays of individual exemplars of racial outgroups resist extinction, whereas conditioned fear towards ingroup exemplars readily extinguish. Navarrete et al [51] extended these findings by demonstrating that conditioned fear towards faces of outgroup exemplars resists extinction solely when the outgroup targets are male and not female, which is consistent with the male warrior hypothesis.…”
Section: Fear and Prejudice Against Outgroup Malesmentioning
confidence: 57%
“…In a similar way, presentation of aversive stimuli during conditioning may activate negative stereotypes of racial out-group faces or negative affect that in turn may prime these stimuli to form stronger associations with the negative US -resulting in slower extinction of fear learning. However, this alternative explanation is qualified by findings that explicit and implicit race biases do not correlate with resistance to extinction of fear-learning to racial out-group faces (Navarrete et al, 2009;Olsson et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…This interpretation was somewhat qualified by a recent study which replicated Olsson findings with Black and White in-group and out-group stimuli. Resistance to extinction was found for fear conditioned to male out-group faces, but not for fear conditioned to female out-group faces (Navarrete et al, 2009). This finding may be interpreted as a demonstration of the specificity of prepared learning due to the greater threat out-group males posed throughout human evolution (Manson & Wrangham, 1991).…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, research has shown that electrodermal conditioning to pictures of faces, with electric shock as the unconditioned stimulus, worked best in the case of pictures of angry males, better than with happy pictures or pictures of angry females (Öhman & Dimberg, 1978). Moreover, in a fear-conditioning experiment, it has been observed that conditioned fear to the face of a male out-group target resists extinction, but conditioned fear toward the face of a female outgroup target readily extinguished (Navarrete et al, 2009). Rotteveel and Phaf (2004) reported that their female sample reacted faster to male than to female faces, particularly to angry ones.…”
Section: Sex Of the Actor And Sex Of The Observermentioning
confidence: 99%